Comparison of the oral, rectal, and vaginal immunization routes for induction of antibodies in rectal and genital tract secretions of women. - Kozlowski, P A (1997)
To determine which mucosal immunization routes may be optimal for induction of antibodies in the rectum and female genital tract, groups of women were immunized a total of three times either orally, rectally, or vaginally with a cholera vaccine containing killed Vibrio cholerae cells and the recombinant cholera toxin B (CTB) subunit. Systemic and mucosal antibody responses were assessed at 2-week intervals by quantitation of CTB-specific antibodies in serum and in secretions collected directly from mucosal surfaces of the oral cavity, rectum, cervix, and vagina with absorbent wicks. The three immunization routes increased levels of specific immunoglobulin G (IgG) in serum and specific IgA in saliva to similar extents. Rectal immunization was superior to other routes for inducing high levels of specific IgA and IgG in rectal secretions but was least effective for generating antibodies in female genital tract secretions. Only vaginal immunization significantly increased both specific IgA and specific IgG in both the cervix and the vagina. In addition, local production of CTB-specific IgG in the genital tract could be demonstrated only in vaginally immunized women. Vaginal immunization did not generate antibodies in the rectum, however. Thus, generation of optimal immune responses to sexually transmitted organisms in both the rectal and the genital mucosae of women may require local immunization at both of these sites.